COASTAL CLEAN UP BERSAMA SISWA/I SD DAN SMP SEBAGAI PEWARIS LINGKUNGAN DALAM MENJAGA EKOSISTEM PESISIR SEBAGAI IMPLEMENTASI SDG'S 14 - Asriyana; Dedy Oetama; Haslianti; Chairun Annisa Aryanti; Wa Jali; Adi Imam Wahyudi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The amount of plastic waste polluting Indonesia’s waters stands at 400,000 tonnes per year, confirming that humans are the largest source of this waste. Microplastics have a serious impact on the marine life that ingests them. Early prevention is essential by reducing plastic waste through initiatives such as coastal clean-ups. This aligns with SDG 14 (Life Below Water) to enhance the sustainability of marine and fisheries ecosystems. The activity took place on the Lalowaru coast, South Konawe, with participants from students of SDN 4 Moramo Utara and SMPN 37 Moramo. The stages of the activity included coordination with the schools, preparation of equipment, group allocation, implementation of the activity, and evaluation. It began with an awareness-raising session for the pupils on the importance of protecting marine ecosystems, followed by a beach clean-up to collect inorganic waste using bin bags. The majority of the waste consisted of plastic food packaging. The collected waste was then weighed. Most participants took part in the coastal clean-up with enthusiasm. They demonstrated their understanding by explaining and providing examples of the consequences of damage to these ecosystems. Therefore, sustainable marine education, whether through formal or non-formal channels, is essential as a step towards supporting sustainable marine development.